O distanciamento psicológico e a percepção de sucesso em projetos - Bartholomeu Filho, Jaime (2023)
More than 30% of projects do not meet their original objectives, about 50% will not meet one or more requirements, only about 40% of projects will be able to meet planned objectives. Therefore, achieving project success is a huge challenge faced by organizations and professionals. This thesis aims to present a framework that will enable project management professionals to increase the perception (probability) of success in projects. The framework was developed by carrying out experiments that sought the causal relationship between the perception of project success and the psychological distance of those involved. The experiments were based on two independent and interrelated studies. The first study defined the criteria for success in projects, which were limited to meeting cost and time requirements, which are objective and quantifiable. Abstract criteria linked to interested parties were not considered, due to the lack of formal methods for evaluation, lack of methodology, controlled and easily implemented procedures. The project environment promotes the interaction of several actors, with different expectations, objectives and motivations, subject to different conditions throughout their life cycle. The different operational conditions and the resulting relationships subject those involved to different psychological distances and, according to the CLT (Constructal Level Theory), directly affect individual behavior and shape behaviors that alter individual and group processes. The second study sought to understand the effects of psychological distancing, under the concepts of the CLT, of how these distances in relation to events, people, objects and locations, affect the vision, interpretation and behavior of individuals subjected to these distances and, therefore, alter their perceptions, interpretations and judgments. As the project environment is prodigal in creating “psychological distances”, throughout its life cycle, then the effects, on the perception of success in projects, must be understood differently by those submitted to different psychological distances. XI The results of the experiment showed that there is a causal relationship between psychological distance and the perception of project success, with a greater (lesser) perception of success being attributed to the condition of psychological proximity (distance). This work contributes with professionals in project management to increase the perception of success in projects, guiding them in creating procedural structures and promoting interactions, between those involved with the projects, with reduction of psychological distances and, with that, obtaining a greater perception Of success. Academically, it seeks to encourage deeper studies on the subject, in a possible new frontier of knowledge in project management. This thesis is considered empirical in nature, with a quantitative approach and an experimental strategy, developing a technological artifact (framework) and is part of the Project Management research line of the PPGP-UNINOVE, in the context of research on Innovation in Projects.